Pengaruh Terapi Massage terhadap Intensitas Nyeri Bahu, Ketegangan Otot dan Kecemasan Pada Pasien Stroke (Systematic Review) - Harum Nurdinah; Rizanda Machmud; Esi Afriyanti (FORIKES, 2021)
Background: Post-stroke patients experience several complaints, namely shoulder pain 72.5%, muscle tension 66.7% and anxiety 23.7%. Massage is an alternative or complementary therapy that can be given. However, massage therapy is still rarely implemented in health services to be able to deal with these problems. Objective: To analyze the effect of multiple massage therapies on shoulder pain intensity, muscle tension, and anxiety for stroke patients. Methods: A search on electronic media by using specific keywords in five databases of published journals namely ProQuest (n=50), Elsevier (n=117), SAGE (n=20), NCBI (n=41), and Wiley Online Library (n=109). Using the Joanna Briggs Institute’s analytical approach, 9 journals were analyzed. Results: Based on the literature that has been obtained massage therapy that can be given to intensity of shoulder pain, muscle tension and anxiety for stroke patients is Chinese therapy (Tui Na) research results of Yang et al., (2017), ayurvedic massage research results Sankaran et al. , (2019), Traditional Thai Massage (TTM) research results from Thanakiatpinyo et al., (2014), Touch Massage (TM) research results from Lämås et al., (2016), tactile massage research results Cronfalk et al., (2020) and Slow Stroke Back Massage (SSBM) research results by Tannous et al., (2015), Atashi et al., (2013), and Atashi et al., (2012) and Kousalya, (2012). Conclusion: Traditional Thai Massage (TTM) is very effective for reducing the intensity of shoulder pain, muscle tension and anxiety in stroke patients. Recommendation: Health services need to make SOP to provide massage therapy for stroke patients.Keywords: massage; shoulder pain; muscle tension; anxiety; strokeABSTRAKLatar belakang: Pasien pasca stroke mengalami beberapa keluhan yaitu nyeri bahu 72, 5%, ketegangan otot 66, 7% dan kecemasan 23, 7%. Massage merupakan salah satu terapi alternatif atau komplementer yang dapat diberikan. Namun, terapi massage ini masih jarang dilaksanakan di pelayanan kesehatan untuk dapat menangani masalah tersebut. Tujuan: Menganalisis pengaruh terapi massage terhadap intensitas nyeri bahu, ketegangan otot dan kecemasan pada pasien stroke. Metode: Pencarian dengan media elektronik menggunakan kata kunci yang spesifik pada lima database jurnal terpublikasi yaitu ProQuest (n=50), Elsevier (n=117), SAGE (n=20), NCBI (n=41), dan Wiley Online Library (n=109). Menggunakan pendekatan analisis Joanna Briggs Institute didapatkan 9 artikel yang dianalisis. Hasil: Berdasarkan literatur yang telah didapatkan terapi massage yang bisa diberikan untuk mengurangi intensitas nyeri bahu, ketegangan otot dan kecemasan pada pasien stroke adalah terapi pijat Cina (Tui Na) hasil penelitian Yang et al., (2017), ayurvedic massage hasil penelitian Sankaran et al., (2019), Traditional Thai Massage (TTM) hasil penelitian Thanakiatpinyo et al., (2014), Touch Massage (TM) hasil penelitian Lämås et al., (2016), tactile massage hasil penelitian Cronfalk et al., (2020) dan Slow Stroke Back Massage (SSBM) hasil penelitian Tannous et al., (2015), Atashi et al., (2013), dan Atashi et al., (2012) serta Kousalya, (2012). Kesimpulan: Terapi massage Teknik Traditional Thai Massage (TTM) sangat efektif untuk mengurangi intensitas nyeri bahu, ketegangan otot dan kecemasan pada pasien stroke. Rekomendasi: Pelayanan kesehatan perlu membuat SOP untuk pemberian terapi massage pada pasien stroke.Kata kunci: massage; nyeri bahu; ketegangan otot; kecemasan; stroke